The Impact of the Chinese Diaspora in the U.S. on the American View of China - Misiuna, Jan (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The first Chinese immigrants arrived in the United States in the 1820s and initially their presence did not result in improving the American perception of China. On the contrary – intense immigration from China led to the development of racist and xenophobic attitudes towards the Chinese (Yellow Peril), which culminated in the Chinese Exclusion Act of 1882. During the Second World War, China became an important ally of the United States, which triggered a succession of changes to laws barring Chinese immigration (Magnuson Act). Contemporary Chinese Americans – particularly Taiwanese Americans – can be located in the upper spheres of immigrant population: they are considered to be a well-educated and affluent group. This paper presents the historical and contemporary socio-economic characteristics of the Sino-American population set against a historical and legal background.